In vitro penetration activity of ionic liquid-Gnetum gnemon seed extract loaded solid lipid nanoparticles - Elsa Trinovita, Maesya Rachmawati, Sutriyo Sutriyo, Abdul Munim (Journal of Applied Pharmaceutical Science, 2019)
Gnetum gnemon L. (Melinjo) seeds have high trans-resveratrol, which was known to have poor skin absorption ability. This study was performed to evaluate the skin absorption of ionic liquid-melinjo seed extract (IL-MSE) loaded solid lipid nanoparticles (SLN). The SLNs was formulated with glyceryl monostearate as the lipid ingredient, ceteareth-25, ceteareth-6, stearyl alcohol, an aqueous phase, and 10% melinjo seed extract. The SLNs were prepared by modification of high-pressure homogenization. The polydispersity index (PDI), zeta potential, entrapment efficiency (EE), particle size (PS), and morphological scanning electron microscopy (SEM) were evaluated. The in vitro penetration of IL-MSE SLN was carried out by using the Franz cell diffusion method. The SLNs formulations showed an average of particles size about 794 nm, and with high lipid and surfactant, the content could contributing to high entrapment efficiency to almost 89%. Even though the polydispersity index of SLN was 1.229, and zeta potential measurement was 62.56 mV. Up to 45% of the trans-resveratrol penetrated through the skin after 8 hours of the test run. The IL-MSE loaded to SLNs could improve the absorption of trans-resveratrol through the skin.
Keywords: Franz cell diffusion, Gnetum gnemon, ionic liquid-melinjo seed extract, solid lipid nanoparticles, trans-resveratrol.